Looking For Divine Account On Psychological and Philosophical Intuition - Mumtaza Hafidz, Alya (Asian Journal of Social and Humanities, 2023)
In its history, intuition has a variety of spectrum of meaning from various fields of study. Most associate it with mystical things that are intervened by supernatural powers. Especially with knowledge that comes suddenly (Eureka/Ilham moment) makes intuition not infrequently connected with Divine Agents. As a process, debate about intuition often occurs in the field of philosophical and psychological studies. Both have a fundamental difference, both from the meaning of the process and knowledge they produce. However, regardless of these differences, philosophical intuition and psychological intuition have a fundamental equality that is far related to something that is mystical. This article will describe the intuition from two perspectives then analyze the differences and similarities of intuition in the study of philosophy and psychology to find the existence of divine interference